Harvest technology and labour supply in Britain, 1790-1870 - Collins, E. J. T. (1970)
This thesis tries to establish a functional relationship between the supply and supply price of labour, product-mix and choice of technology in British agriculture during the period 1700-1870. The desiderata, increased production and lower unit production costs were in many respects incompatible with those of full-employment and greater social welfare. Historians have been primarily concerned with just one aspect of this problem, namely structural unemployment during the winter months. This is to ignore that the chief limiting factor on increased production may often have been the capacity of the labour force during the summer work-bottlenecks. This thesis argues that over a large part of the proto-industrial period (1790-1870), British agriculture was afflicted by sometimes very serious labour shortages in the summer work peaks. It goes on to a detailed case-study of labour supply and technological change in the corn harvest, the farm operation which historically has always created the exceptional demand for labour, and in which labour shortages were soonest likely to develop. It demonstrates that initially, at least, and for some time after 1851, when reaping machinery became available, the majority of farmers obtained their labour and labour cost-savings not through mechanization but by a more intensive use of labour (the more thorough exploitation of child and female labour, greater dependence on migrant harvesters and the introduction of piecework), and, when the supply of labour became inelastic, by the 'intermediate technology’ of improved hand tools, in particular the substitution of the faster-working scythe and heavy hook for the traditional sickle and reap hook. The advantages of this strategy were that it conserved capital, that it did not disrupt other work schedules, and perhaps most important, that it averted unemployment over what for the majority of farm labourers and their families was the key earnings period of the year. It met the requirements for a technology which was discontinuous enough to guarantee production and flexible enough to guarantee employment. The conclusion is that there is a phase of economic development in which factor proportions render a scythe economically and socially more useful than a reaping machine.